The View from Afar - Levi-Strauss Claude (Penguin Books, 1985)
A masterly short treatise on anthropology and a complex portrait of a uniquely penetrating writer. Preface, The Innate and the Acquired, Family and Marriage and Kinship, The Environment and Its Representation, Beliefs and Myths and Rites, Constraint and Freedom, References, Acknowledgements, Index.